Edukasi Pengetahuan KIA dan Kesehatan Lingkungan Dalam Upaya Peningkatan Derajat Kesehatan Pada Masyarakat - Nurul Aliah Alwy, St.; Toalu, Apdiani (Lembaga Penelitian dan Pengabdian Masyarakat,Politeknik Sandi Karsa, 2023)
Background: Health is often overlooked, and we will feel how much it exists when we lose the pleasure of health. Health is not everything, but everything we have will mean nothing without health. This service aims to provide education on MCH knowledge and environmental health to improve the degree of health in the community. The implementation method conducts education and evaluates the community about increasing MCH knowledge and environmental health. Results: From the results of the pretest analysis, there is an increase in knowledge after being given communication, education, and information. Conclusion: The knowledge of MCH and environmental sanitation is increasing. There needs to be more coordination between the government and community members in improving the degree of health, especially environmental health.